The influence of professional identity on work engagement among nurses working in nursing homes in China. (16th June 2022) - Zhang, Hongchen; Li, Huiju; Tian, Weihua; Liu, Wen; Yang, Yanwei
Abstract: Aim: To assess the influence of professional identity on work engagement among nurses working in nursing homes in China. Background: China is faced with an increasingly ageing population. There is a shortage of adequately trained nursing personnel and a high turnover rate among nurses. Work engagement is a key factor in improving nurses' performance and improving professional identity is critical to increase work productivity and satisfaction. Methods: We conducted a cross‐sectional survey of 272 nurses working in nursing homes. And the data were analysed by descriptive analyses, univariate analysis and Multiple regression analyses. Results: The overall average work engagement score was 3.99 ± 1.04. Professional identity was the only factor that significantly influenced the 'vigour' and 'absorption' of nurses. Age, ethnicity and professional identity were significant predictors of 'dedication'. Conclusions: A positive professional identity can lead to a better work engagement among nurses working in nursing homes in China. Implications for Nursing Management: To enhance the work engagement of nurses working in nursing homes, nursing leaders should create a respectful and equal work environment, create a favourable image of the industry and the profession and strengthen training to improve the professional identity.